Basic information services: Successes and challenges - Pons, Amadeu (Anuario ThinkEPI, 2008)
Advanced information services developed in Spanish public libraries are examined, as well as some of the information resources widely available online. The author calls for an organic relationship between the public library system and the telephone-based information services provided by local and regional authorities.